Knowledge, Perceptions, and Attitudes of Central Government Civil Servants towards the National Capital (IKN) Relocation - Renny Savitri; Madya Putra Yaumil Ahad; Benedicta Retna Cahyarini; Ladiatno Samsara; Hasna Melani Puspasari (Puslatbang KDOD Lembaga Administrasi Negara, 2023)
Various discussions and studies from different sectors have emerged as a reaction to the relocation of the Indonesian capital city from economic, transportation, and environmental perspectives. However, not many articles discuss civil servants as one of the groups directly affected by the relocation policy. This paper describes the condition and correlation of civil servants' knowledge, perceptions and attitudes toward the IKN relocation policy. This research uses quantitative descriptive research methods, which were conducted by distributing surveys to Central Government Civil Servants based in Greater Jakarta. The survey results stated that civil servants had relatively excellent knowledge regarding IKN relocation, while civil servants' perceptions of IKN transfers tended to be negative. Regarding attitude, 48% of respondents wanted to be transferred with special compensation. Based on the analysis of the relationship between three aspects, it is known that crosstabulation analysis on knowledge and perception affects the attitudes of civil servants regarding the IKN relocation policy. Meanwhile, cross-tabulation analysis between knowledge and perception does not affect each other. Finally, from the results, to increase the knowledge and perception of civil servants, the government needs to increase socialization among civil servants regarding the IKN relocation policy and update the information regularly and massively, especially in the compensation that is more in favour of civil servants